Degenerative changes of the wrist in mixed martial arts and boxing based on the three column theory - Schiffner, E.; Hilsmann, F.; Lakomek, F.; Beyersdorf, C.; Windolf, J.; Latz, D. (The Physician and Sportsmedicine, 2024)
Objective Mixed Martial Arts (MMA) is a relatively young combat sport. In contrast to classic boxing, MMA combines techniques of grappling and striking. However, characteristic long-term effects of MMA on the wrist are discussed controversially. Aim of this study was to elucidate characteristic degenerative changes of the wrist from MMA fighters in comparison to classic boxers.